Social Support is Related to the Mental Health of Migrant Nursing Student - Nataria yulianie; Wahidyanti Rahayu Hastutiningtyas (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
First year of college students relocating away from home frequently encounter diverse challenges while adapting to a new academic and social environment. This transition often impacts their psychological well-being, highlighting the need for protective factors to sustain and enhance mental health. This study aims to analyze the correlation between social support and mental health among these students. Utilizing a descriptive analysis method, the research focused on a population of 125 students, with 95 participant selected trough purposive sampling. Data were gathered via social support and mental health questionnaires. Analysis using the Spearman rank sum test yielded a p-value of 0.003, indicating a significant relationship between the variables. Furthermore, a correlation coefficient of 0.979 indicates a strong positive association, suggesting that diminished social support correspond with poorer mental health outcomes. Further research in developing robust mentoring, and support programs as promotional and preventive measure to safeguard student’s mental health within higher education settings is recommended.